CD32-dependent platelet activation by a drug-dependent antibody to glycoprotein IIb/IIIa antagonists - Pedicord, Donna L.; Dicker, Ira; O’Neil, Karyn; Breth, Leah; Wynn, Richard; Hollis, Greogory F.; Billheimer, Jeffrey T.; Stern, Andrew M.; Seiffert, Dietmar (Thrombosis and Haemostasis, 2003)
Thrombocytopenia is observed with a frequency of up to 2% in patients treated with glycoprotein (GP) IIb/IIIa antagonists. We recently provided evidence that thrombocytopenia is caused by antibody binding to drug-induced conformational changes in GP IIb/IIIa. Here, we report that a murine monoclonal antibody binds to GP IIb/IIIa in an antagonist-dependent manner and activates platelets. Platelet stimulation is associated with a disruption of the phospholipid asymmetry, resulting in the assembly of catalytic active intrinsic Xase and prothrombinase complexes. Further mechanistic studies revealed that this response is (I) mediated in cis, (II) not associated with the formation of pro-thrombotic microparticles, and (III) requires intact platelet signaling and (IV) is blocked by increases in cAMP. The prothrombotic response is not observed using F(ab’)2 fragments and is blocked by incubation of platelets with neutralizing antibodies to the platelet FcγRIIa receptor (CD 32). Taken together, these observations suggest that GPIIb/IIIa antagonist-dependent antibody binding to the platelet fibrinogen receptor has the propensity to lead to CD32-mediated platelet activation and accelerated platelet clearance, leading to thrombocytopenia.
Keywords: Platelets drug-dependent antibodies glycoprotein IIb/IIIa thrombocytopenia